(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
The induction of acute inflammation in the lung tissue is triggered by lipopolysaccharide (LPS)-mediated activation of the TLR4 receptor. The combination of Tithonia diversifolia (T), Moringa oleifera (M), and Curcuma longa (C) extracts holds potential for synergistic anti-inflammatory and antioxidant effects. This study aimed to evaluate the effect of the aqueous TMC extract combination on reducing malondialdehyde (MDA) levels and enhancing Superoxide Dismutase (SOD) and Nuclear Factor Erythroid-2 Related Factor 2 (NRF2) expression in LPS-induced acute lung injury (ALI) in BALB/c mice. Thirty-six BALB/c mice were divided into five groups: negative control, LPS positive control, and three treatment groups receiving varying doses of the combined extract (TMC-1: 500/300/200; TMC-2: 200/500/300; TMC-3: 300/200/500 mg/kg BW). Treatments were administered orally for 14 days, followed by intraperitoneal LPS induction (0.5 mg/kg BW). Extract combination (TMC) significantly mitigated LPS-induced oxidative stress in a mouse acute lung injury model. Post-LPS therapy reduced MDA levels dose-dependently (16.96–8.68% vs. LPS 36.52%), restored SOD activity near normal (5.74–13.84% vs. LPS 25.23%), and normalized NRF2 expression (8.68–9.58% vs. LPS 17.11%). The TMC combination significantly reduced MDA levels and normalized the NRF2–SOD pathway, with the strongest SOD restoration at P2 (5.74%). These results confirm the role of TMC in strengthening the endogenous antioxidant system. This study provides scientific evidence for the development of the TMC extract combination as a potential phytopharmaceutical agent to mitigate oxidative stress and support tissue repair in inflammatory conditions such as ALI. Ultimately, this research supports UN SDG 3 (Targets 3.4 and 3.b) by developing an affordable respiratory protective agent, while simultaneously advancing SDG 15 through the sustainable pharmacological utilization of local plant biodiversity.